PENGARUH KEGIATAN MENARI TERHADAP KEPERCAYAAN DIRI ANAK USIA 4-5 TAHUN DI KB NURUL ANWAR PEKANBARU - Badriyah Badriyah; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) To determine the child's confidence before the application of dancing children aged 4-5 years in KB Nurul Anwar Pekanbaru. 2) To determine the child's self confidence after the adoption of dancing children aged 4-5 years in KB Nurul Anwar Pekanbaru. 3) To determine whether there is influence of dancing on the confidence of children aged 4-5 years in KB Nurul Anwar Pekanbaru. 4) To determine the influence of dancing on the confidence of children aged 4-5 years in KB Nurul Anwar Pekanbaru. This type of research used in this research is the experimental approach of a study that sought influence of certain variables on other variables in strictly controlled conditions. The research sample is graders B consisted of 20 children, consisted of 7 men and 13 women. Based on the survey results revealed that 1) The confidence of children aged 4-5 years in KB Nurul Anwar Pekanbaru before treatment is given in the form of dancing is low because more than most children look happy, not in the spirit of learning activities that tend to dull. 2) The confidence of children aged 4-5 years in KB Nurul Anwar Pekanbaru after treatment is given in the form of dancing has increased and is high because more than most children in the spirit of learning activities, children's dancing pleasure in activities that are moving the body freely. 3) The dancing has a significant impact on the confidence of children aged 4-5 years in KB Nurul Anwar Pekanbaru. It can be seen that there are differences in the form of increased confidence in children before and after treatment. 4) Activity dancing has a 26.25% influence on the confidence of children aged 4-5 years in KB Nurul Anwar Pekanbaru.Keywords: Dancing, Confidence